2015
DOI: 10.1136/annrheumdis-2014-206966
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-anti-trypsin-Fc fusion protein ameliorates gouty arthritis by reducing release and extracellular processing of IL-1β and by the induction of endogenous IL-1Ra

Abstract: A single low dose of AAT-Fc is highly effective in reducing joint inflammation in this model of acute gouty arthritis. Considering the long-term safety of plasma-derived AAT use in humans, subcutaneous AAT-Fc emerges as a promising therapy for gout attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 45 publications
0
38
0
3
Order By: Relevance
“…In addition, AAT possesses a broad spectrum of anti-inflammatory (37,39) and immunomodulatory properties, unrelated to protease inhibition (37,40), including elevation of cAMP in target cells (41) and inhibition of the aggrecanase ADAMTS-4 (42). A recent study reported the antiarthritic properties of an ATT-Fc fusion protein in murine acute gouty arthritis with reduced release of IL-1b and induction of IL-1 receptor antagonist (43). Equally pertinent is the observation that AAT treatment reduces autoimmunity and delays arthritis development in a mouse model of collagen-induced arthritis (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AAT possesses a broad spectrum of anti-inflammatory (37,39) and immunomodulatory properties, unrelated to protease inhibition (37,40), including elevation of cAMP in target cells (41) and inhibition of the aggrecanase ADAMTS-4 (42). A recent study reported the antiarthritic properties of an ATT-Fc fusion protein in murine acute gouty arthritis with reduced release of IL-1b and induction of IL-1 receptor antagonist (43). Equally pertinent is the observation that AAT treatment reduces autoimmunity and delays arthritis development in a mouse model of collagen-induced arthritis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Gout arthritis was induced in mice through i.a. injection of MSU and palmitate (C16) as previously described (43,44). Hyperuricemia was induced in mice through uricase inhibition with oxonic acid (45,46).…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, such a patent application was issued describing the production of Fc-fusion recombinant AAT molecule, later also mentioned to have superior serum half-life to the wild-type version of the protein, while still retaining its anti-inflammatory properties. [54] …”
Section: Patents On Aat Productionmentioning
confidence: 97%
“…[27,31,73] The first patent to describe the use of AAT for the treatment of bacterial infection was published in 2005, [74] describing the administration of AAT as a means of protection from and treatment of mycobacterial infection. On this ground, one patent application was published in 2012 and two in 2014, all of which describe the construct of an AAT-Fc fusion molecule, already known to be anti-inflammatory and cytoprotective, [43,44,54] to treat and prevent mycobacterial infection.…”
Section: Patents On Reduction Of Bacterial Burdenmentioning
confidence: 98%